Factores asociados a la violencia de género en mujeres de Iquitos - Aquino Ruiz, Mili (2025)
The objective was to determine the factors associated with gender violence in women in Iquitos. The quantitative method was used with a correlational and retrospective descriptive design. The population and sample were made up of the 570 women treated at the Women's Emergency Center in the city of Iquitos during the period 2018 to 2019. The technique used was the documentary review and the instruments were the data registration form for individual and social factors. the women treated at the Iquitos Women's Emergency Center and the data record sheet on the type of violence exercised against women. For the univariate analysis, descriptive statistics were used, and for the bivariate analysis, the non-parametric inferential statistics of free distribution Chi Square (X2) were used. The results were: 61.6% were between 19 and 44 years old, 25.6% had completed secondary school, 92.1% came from urban areas, 68.4% had no history of intimate partner violence, 74.7% % the condition that generated the violence was sobriety, 56.5% the reason that generated the violence was “they have access to the person”, 84.7% were single, the 52.6% did not have an occupation, 61.2% did not receive physical violence and 92.3% of the participants were victims of psychological violence. In conclusion: it was demonstrated that there is a relationship between physical violence with: age (p = 0.003), history of intimate partner violence (p = 0.038) and marital status (p = 0.010), and with psychological violence, it was demonstrated that There is a relationship with: age (p = 0.002), the reason that generated the violence (p = 0.015) and occupation (p = 0.010).